A quarta revolução industrial e os impactos nos contratos de emprego - Sales, Rafael Henrique Dias (2023)
New technologies have taken great strides in several areas, uniting evolutions in the physical, digital and biological worlds at the same time. This has led to the constant emergence of new forms of replacing human labor, as well as new business models, which in turn have modified the traditional forms of contracting labor. These changes are reflections of what has been called by the doctrine, among others, Klaus Schwab, the fourth industrial revolution, which includes advances in traditional business areas, especially manufacturing, with the development of robotics, artificial intelligence and automation; as well as the emergence of new business models, developed from work intermediated by digital platforms. The first reflections of the fourth industrial revolution, inherent to the replacement of human labor by machines, generate some legal discussions, especially with regard to the protection that should be given to workers, in view of the provisions of art. 7, XXVII of the Federal Constitution. This constitutional device has not yet been regulated, but there are bills and Direct Action of Unconstitutionality by Omission (ADO) filed with this objective, which were analyzed in the course of this work. The other reflexes of the fourth industrial revolution are especially in the emergence of new business models, which mostly aim to give a new look to the legal relationship between contractor and contractor, trying to move away from the intuitive rules of labor law, that is, seeking deprive the working class of the entire list of fundamental rights of art. 7 and others of the Federal Constitution and the CLT, as warned by Gabriela Neves Delgado and Bruna Vasconcelos de Carvalho. Thus, legal elements were gathered to discuss the nature of these relationships, with an investigation being carried out to find out whether legal subordination can be extended via algorithmic subordination, as advocated by Rodrigo Carelli, and thus guaranteeing the same protective arsenal for employees in general, or whether the solution would be to propose a new protective model for this new class of workers, which many call the precariat, a concept developed by Guy Standing and absorbed in Brazil by Ricardo Antunes. In order to reach the legal discussions, in the propaedeutics of the present work, an attempt was made to make a historical rescue of each stage of the industrial revolutions, from the writings of Friederich Engels, making a sociological and economic analysis regarding the technological advances and the its mismatch with human evolution. At the heart of the work, it was concluded that it is essential to regulate art. 7, XXVII of the CF, as well as that there is a jurisprudential evolution to extend the concept of subordination, housing the algorithm, or that there is a regulation of the provision of services via digital platforms, aiming to guarantee the extension of fundamental labor rights to all workers.